2019
DOI: 10.3390/su11030896
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Vernacular Architecture to the Sustainability: A Comparative Study between the Contemporary Areas and the Old Quarter of a Mediterranean City

Abstract: The strongest point of vernacular architecture is the harmony between environment and buildings. Mediterranean vernacular architecture is harmonized with its local context, including culture and traditions. In addition, it respects environmental and climatic factors, construction materials, and morphology. In the past, people in Palestine built their houses according to their possibilities, needs, available materials, topography, and culture. Without any control from the government or any legal limitations or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 9 publications
1
42
0
1
Order By: Relevance
“…This high level of similarity qualifies the vernacular to be a great source of ideas for architecture to produce a nature-like sustainable architecture or biomimetic architecture. These aspects have also been explored in the recent study by Al Tawayha, Braganca, and Mateus (2019) which showed that strategies of vernacular architecture induce in the nature like sustainability which can help progress the architectural design in a more optimized manner.…”
Section: Nature Design Principles and Yaama Mosque: A Comparative Anamentioning
confidence: 99%
“…This high level of similarity qualifies the vernacular to be a great source of ideas for architecture to produce a nature-like sustainable architecture or biomimetic architecture. These aspects have also been explored in the recent study by Al Tawayha, Braganca, and Mateus (2019) which showed that strategies of vernacular architecture induce in the nature like sustainability which can help progress the architectural design in a more optimized manner.…”
Section: Nature Design Principles and Yaama Mosque: A Comparative Anamentioning
confidence: 99%
“…For this reason, a large continuing body of works has demonstrated its values and why vernacular architecture should be taken seriously in architectural practice, for example, References [1,14,15]. The most frequent expression which summarizes the aims of the research includes, 'lessons from vernacular architecture' and 'learning from the vernacular' for example, References [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. As such, it has simply become related to specific arguments such as positioning it as a didactic alternative to the contemporary architecture which is associated with uncontrollable greenhouse gas emission, disproportionate energy consumption and unsustainable use of earth's resources [1,27,28].…”
Section: Vernacular Architecture and The Sustainability Discoursementioning
confidence: 99%
“…The Rawshan is a true reflection of this tradition and has enjoyed a secular importance in the middle eastern domestic architecture. This criterion has been investigated by many scholars in the same field [5,7,8,11,[13][14][15][16][17]. However, other researchers, for example Samuels [18], overlooked the social aspects in their research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main factors that influence vernacular architecture include local environmental conditions, materials, and construction techniques as well as building occupant needs [2]. In most cases, conventional buildings are built to house and protect inhabitants from environmental factors while maintaining a level of harmony with the surrounding environment and prevalent culture [3][4][5]. Vernacular architecture exemplifies the highest form of sustainable building, as it typically employs exclusively locally sourced materials and environmentally friendly technologies [6].…”
Section: Introductionmentioning
confidence: 99%